Pengaruh Penggunaan Media Audio Visual Terhadap Hasil Belajar Kosa Kata Bahasa Inggris Siswa Kelas II MI Dwi Dasa Warsa - Edy Kurniawan; Mokhammad Nizzam; M. Alfin Fatikh; Muhammad Husnur Rofiq (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
The problem in this research is the lack of mastery of students ‘English vocabulary, the teacher’s lack of creativity in using learning media, and students’ assumption that English lessons are difficult and ultimately ignored. Formulation of the problem “how the influence of the use of audio-visual media on learning outcomes of English vocabulary students in grade II MI Dwi Dasa Warsa. The study aims to determine the effect of audio-visual media on learning outcomes of English vocabulary material Pets and Wild Animals in Class II MI Dwi Dasa Warsa This study is quasi-experimental design research with one group pre-test design research. The population in this study was all students in MI Dwi Dasa Warsa with a total of 273 students, while the sample were all students of class II MI Dwi Dasa Warsa amounting to 37 students. Data were analyzed using the Mann-Whitney test formula. From the hypothesis testing, it can be concluded that there is a significant influence of the use of audiovisual media on the learning outcomes of English vocabulary material Pets and Wild Animals.